The Role of Islamic Religious Education Teachers in Moral Development in MTs. Private Al-Azhar Medan Sunggal - Eka Rahmatul Aulia; Fuji Rahmadi P; Bachtiar Siregar (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2022)
The role of the Islamic religious education teacher is an effort made by a teacher to foster, nurture and direct students to always understand the teachings of Islam as a whole, understand its meaning and purpose, carry out what was ordered by Allah and His Apostle then become a prohibition in order to apply it in life. daily. It is very important to instill the values of Islamic education in the family. Every parent wants their child to be a pious child, which gives them pleasure and pride. This research was conducted in MTs. Private Al-Azhar Medan Sunggal which aims to find out what roles are played by Islamic Religious Education Teachers in Moral Development, find out how students' morals are, and know the factors of student moral development at Mts. Private Al-Azhar Medan Sunggal. This study uses a qualitative method with field research. The results showed that the teacher showed efforts to provide Islamic religious education in moral development to all students with formal education about religion and morality. The ability of students regarding education in moral development is emphasized Faith in God, Obedience to God absolutely, namely carrying out all His commands and Loving God above all else.